THE ROLE OF HOSPITAL SERVICE QUALITY IN THE NATIONAL HEALTH INSURANCE / JAMINAN KESEHATAN NASIONAL (JKN) ERA AND THE COVID-19 PANDEMIC - Ilma, Aqlya Zuhra; Sugiarto, Catur (Universitas Brawijaya, Indonesia, 2023)
Fewer people are visiting the outpatient clinics at Pandan Arang Hospital, Boyolali, due to the Covid-19 pandemic and the hospital class transition, with the exception of the Gastroentero Hepatology (GEH) clinic. The primary focus of this research is to learn how the GEH clinic's administration can improve service quality to attract and retain patients. This research aimed to identify the factors (service quality, customer experience, and perceived value) that lead to trust, satisfaction, and loyalty among consumers and patients when choosing healthcare providers. This study used a Sequential Exploratory design with a mixed-method approach, interviewing GEH's management and consultant doctors first and then sending out questionnaires to 307 patients of the GEH clinic at various times. Based on this research, Pandan Arang Hospital has the necessary facilities and staff to qualify as a type B hospital. Pandan Arang Hospital provided outpatient services during the pandemic, with a separate service flow for Covid-19 and Non-Covid-19 patients, as the World Health Organization and the Ministry of Health recommended. Quantitative studies show a positive and significant connection between service quality, customer experience, and perceived value on trust. Then, there's a powerfully positive connection between service quality, the value customers perceive they receive, and their level of trust in the company. Further, a positive and statistically significant correlation exists between contented customers and continued business.